PENGARUH PERBEDAAN WAKTU PENAHANAN SUHU STABIL TERHADAP KEKERASAN LOGAM - effendi, Sairul (AUSTENIT, 2009)
Hardening to metal is getting good metal properties such as in strength. By heat treatment in 4 stage namely: preheating, post heating, holding time and cooling will be get the strength with special carbon composition. Strength of amutit steels can be reach by heat treatment with holding time and the hardness of this material will be maximum. The hardness in 10, 20, 30, 40 minute after holding time are 60,08 HRC, 62,693 HRC, 64,52 HRC, 65,146 HRC. This information is known that the hardness of amutit steel is influence by holding time and also temperature.